Knowledge of Word Formation for Women Teachers in Kindergarten of Dukuh 02 Mojolaban Sukoharjo: Pemahaman Word Formation Bagi Ibu Guru TK Dukuh 02 Mojolaban Sukoharjo - Tri Widarwati, Nunun; Astuti, Purwani Indri; Wijayava, Ratih (Universitas Lancang Kuning, 2024)
The aims of Community services are to improve knowledge of word formation for women Teachers in Kindergarten of Dukuh 02 so that women Teachers can teach their students. The Method are Pre-test, Presentation, oral, Post-test and discussion of question and answer with face to face. The Media are print-out of Powerpoint, white board , book and bolpoint. The participant are women teachers in Kindergarten of Dukuh 02. The results find that there are improving the knowledge of word formation for women teachers in Kindergarten of Dukuh 02 with 25 point (25%) and the minimum score is 80. The benefit of this program are women teachers in Kindergarten of Dukuh 02 can improve their English skill with word formation Keywords: English, training, word formation